Exploring the Two Coupled Conformational Changes That Activate the Munc18-1/Syntaxin-1 Complex - Gong, Jihong; Wang, Xianping; Cui, Chaoyang; Qin, Yuyang; Jin, Ziqi; Ma, Cong; Yang, Xiaofei (Frontiers in Molecular Neuroscience, 2021)
Calcium-dependent synaptic vesicle exocytosis is mediated by SNARE complex formation. The transition from the Munc18-1/syntaxin-1 complex to the SNARE complex is catalyzed by the Munc13-1 MUN domain and involves at least two conformational changes: opening of the syntaxin-1 linker region and extension of Munc18-1 domain 3a. However, the relationship and the action order of the two conformational changes remain not fully understood. Here, our data show that an open conformation in the syntaxin-1 linker region can bypass the requirement of the MUN NF sequence. In addition, an extended state of Munc18-1 domain 3a can compensate the role of the syntaxin-1 RI sequence. Altogether, the current data strongly support our previous notion that opening of the syntaxin-1 linker region by Munc13-1 is a key step to initiate SNARE complex assembly, and consequently, Munc18-1 domain 3a can extend its conformation to serve as a template for association of synaptobrevin-2 and syntaxin-1.